Mimetic experience in adult learning: an example from simulation–based training - Horcik, Zoya; Durand, Marc (Swiss Journal of Educational Research, 2018)
The aim of this paper is to discuss the relevance of the concept of mimesis in adult learning. We refer to a research conducted during simulation-based training sessions for anaesthetic nurses. The data analysis showed evidence of a specific experience in simulation that we defined as «mimetic experience» that cannot ever be completely reduced to the targeted work. Our results raise the question of distance or “sameness between work activity and training activity, and not only in simulated activity. We suggest that mimetic experience is also present in other learning environments that are considered as «serious»: that is, requiring no explicitly mimetic engagement on the part of the learners.